Development and performance evaluation of a spindle press for oil extraction - Oluwole, F. A.; Abdulrahim, A. T.; Aviara, N. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2007)
A manually operated spindle oil press adaptable to rural areas was designed, constructed using locally available materials and tested to evaluate its performance. The spindle press, which consists of tool frame, power transmission unit made of a spindle and its lever arm, and oil expression unit comprising of the upper and lower press plates and the perforated cage, operates on the principle of power screw to express oil from milled oil seeds. Each of these components was analyzed and the results obtained were used as parameter for sizing and fabrication of the components. The raw material used for testing the developed spindle press was groundnut paste and a nylon clothing material was used as filter. Results of the performance tests carried out on the machine using groundnut paste showed a maximum oil recovery of 78.1% and the cake produced is of the same quality when compared with those produced with the traditional method. Also the oil extraction time is reduced by about 50%.